Mobilising Q methodology within a realist evaluation: Lessons from an empirical study. (October 2019) - Harris, Kevin; Henderson, Steven; Wink, Brian
Realist evaluation and Q methodology are established approaches in social science. However, integration of Q methodology within a realist evaluation is scarce. This article attempts to illustrate (through a recent evaluation) how Q methodology can support a realist evaluation. The article attempts to capture the philosophical compatibility of the two approaches creating an argument for Q's integration within realist evaluation. Through the case study selected (a realist evaluation of an evaluation capacity building framework), the iterative methodological process is presented, capturing a snapshot of the findings from the evaluation. This illuminates how Q met the philosophical aims of a realist evaluation to make sense of how, why and under what circumstances a programme or intervention works. It is argued that Q methodology is entirely suitable for capturing the three key stages in a realist evaluation of developing, testing and refining programme theory. It is intended that this article can contribute to inspire other realist evaluators and methodologists to make use of Q as a tool in their evaluation.